DAMPAK KOMUNIKASI POLITIK DAN OPINI PUBLIK TERHADAP PERILAKU MASYARAKAT - Sitti Rabiatul Wahdaniyah (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
Openness of access to information in the digital era provides opportunities for political parties through tiered structures to build political communication, related to efforts to achieve democratic life and increase the degree of quality of public trust in political parties as a constitutional forum. Through communication of political issues and ideas, political parties seek to obtain a number of individual opinions accumulation openly and form public opinion through an activity in the form of a debate debate, or exchange of information between individuals who are in a group. The impact of political communication and public opinion on people's behavior cannot be generalized, because of the different effects it has on each individual due to differences in age, sex, religion, education, intelligence, occupation, socio-economic class, and so on. In addition, the public is a human being who can accept, reject, question, criticize so that with so many sources of information, the public can compare messages from one media with messages from other media, or with messages from public figures or authorities he trusts.